[Aerial view of Cal Poly campus] (1977)
View of main campus, Spanos Stadium, Dexter Library, Engineering East, Engineering West, Frank E. Pilling Computer Science, Clyde P. Fisher Science, University Union, Mott Gym, North Mountain, Red Brick Dorms, Sierra Madre, Yosemite, Poly "P" - looking east, View of the P